The Effect of Profitability and Dividends on Capital Intensity Moderated by Corporate Social Responsibility - Kesumawati Kesumawati; Maria Magdalena; Herlin Tundjung Setijaningsih (Institut Bisnis dan Informatika Kesatuan, 2025)
Capital intensity is crucial for enhancing competitiveness in Indonesia’s manufacturing sector, yet the influence of financial and non-financial factors remains underexplored. This study aims to examine the direct and simultaneous effects of profitability, dividend policy, and Corporate Social Responsibility on capital intensity in manufacturing firms listed on the Indonesia Stock Exchange from 2019 to 2023. A quantitative approach was employed, using purposive sampling to select 52 firms with complete financial and sustainability reports, resulting in 260 firm-year observations. Data were analyzed using multiple linear regression with robust techniques to address non-normal data distribution. The findings reveal that profitability, measured by Return on Assets, significantly increases capital intensity by enabling fixed asset investments. Dividend policy, measured by Dividend Yield, positively affects capital intensity by signaling financial stability to investors. Corporate Social Responsibility, measured by the sustainability disclosure index, enhances capital intensity through improved efficiency and stakeholder trust. Collectively, these variables significantly influence capital intensity, explaining a substantial portion of its variation. The study concludes that integrating profitability, dividend policy, and Corporate Social Responsibility strengthens capital allocation strategies, offering insights for firms to optimize fixed asset utilization and enhance competitiveness in Indonesia’s manufacturing sector.